Interfacial Engineering of MoxSy via Boron‐Doping for Electrochemical N2‐to‐NH3 Conversion - Alsabban, Merfat M.; Peramaiah, Karthik; Genovese, Alessandro; Ahmad, Rafia; Azofra, Luis Miguel; Ramalingam, Vinoth; Hedhili, Mohamed. N.; Wehbe, Nimer; Cavallo, Luigi; Huang, Kuo‐Wei (Advanced materials (Weinheim), 2024)
The electrocatalytic synthesis of ammonia (NH3) through the nitrogen reduction reaction (NRR) under ambient temperature and pressure is emerging as an alternative approach to the conventional Haber–Bosch process. However, it remains a significant challenge due to poor kinetics, low nitrogen (N2) solubility in aqueous electrolytes, and the competing hydrogen evolution reaction (HER), which can significantly impact NH3 production rates and Faradaic efficiency (FE). Herein, a rationally designed boron‐doped molybdenum sulfide (B‐Mo‐MoxSy) electrocatalyst is reported that effectively enhances N2 reduction to  NH3 with an onset potential of −0.15 V versus RHE, achieving a FE of 78% and an NH3 yield of 5.83 µg h⁻¹ cm⁻2 in a 0.05 m H2SO4(aq). Theoretical studies suggest that the effectiveness of NRR originates from electron density redistribution due to boron (B) doping, which provides an ideal pathway for nitrogenous species to bind with electron‐deficient B sites. This work demonstrates a significant exploration, showing that Mo‐based electrocatalysts are capable of facilitating artificial N2 fixation. A rationally designed boron‐doped molybdenum sulfide (B‐Mo‐MoxSy) electrocatalyst demonstrates improved N2 reduction at an onset potential of −0.15 V versus. RHE, achieving Faradaic efficiencies of 78% and an NH3 yield of 5.83 µg h−1 cm−2 in 0.05 m H2SO4(aq). The outstanding NRR performance is attributed to the phase transition of MoxSy, Mo sites, and B doping, which promotes N2 reduction to NH3.